Analysis of Budget Distribution and Accountability at the Financial Affairs Work Unit (Bidkeu) of the Central Java Regional Police for Fiscal Year 2024 - Salsabilla Devana Putri; Nurfauziah Nurfauziah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the distribution and accountability of the budget at the Financial Division Work Unit (Bidkeu) of the Central Java Regional Police (Polda Jateng) for Fiscal Year 2024. Budget management plays an important role in ensuring transparency, accountability, and effective public financial governance. However, its implementation may face administrative and technical challenges that affect reporting quality. This research uses a qualitative descriptive approach. Data were obtained through interviews, observation, and documentation review, including Budget Implementation Documents (DIPA) and financial reports. The analysis focuses on budget distribution mechanisms, accountability processes, and factors influencing reporting effectiveness. The findings show that budget distribution and accountability have been implemented in accordance with regulations. Budget absorption reached 100 percent, and the Budget Implementation Performance Indicator (IKPA) achieved a very good category. Nevertheless, challenges such as administrative delays, limited understanding of digital financial systems like SAKTI, and system disruptions were identified. Strengthening human resource competencies and optimizing technology are recommended to improve future budget management.